An Exploratory Study of Digital Traditional Folklore and Its Acceptance Among Generation Z in Indonesia - Putri Utami; Hendi Sama (INFOKUM, 2022)
Indonesia is a country with diverse cultures, from Sabang to Merauke. Indonesia's cultural diversity is due to Indonesia being an archipelago with a diversity of ethnicities, cultures, languages, and natural resources. One of the cultures owned by each region is folklore. Folklore is part of the oral literature of folklore, which contains aspects of regional culture that will contribute to the nation's wealth. Folklore is expected to increase pedagogical understanding, especially for Generation Z, so that it can support the learning process both formally and informally and preserve the nation's culture as a provision for applying moral values and character. The use of online media is increasing in urban and rural communities. Communication patterns with online media seem familiar because they are believed to fulfill the need for information and data. Gen Z is a generation that has been interacting with technology since birth. Technology and the internet contributed to their growth. They were born between 1995 and 2012 and have never had the opportunity to live without technology and the internet. The existence of technology and the internet has become a crucial part of their daily lives. This research uses a mixed method with a causalistic quantitative basis, a research model very close to research in other sciences. This approach allows researchers to conduct tests or calculations that can be used in decision-making. With a quantitative approach, this research aims to deliver thorough and empirical results and information.